EVALUASI RETROSPEKTIF PROGRAM KELUARGA HARAPAN (PKH) BIDANG PENDIDIKAN DALAM MENGENTASKAN KEMISKINAN DI KECAMATAN SARANG KABUPATEN REMBANG - Sri Wahyu Pratiwi; Retno Sunu Astuti; R .Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Family Hope Program (PKH) is a program aimed at addressing poverty for the poor through the provision of cash assistance with conditions and criteria that must be met by PKH participants, and PKH participants must commit to carrying out their obligations as PKH recipients. The Family Hope Program (PKH) in Rembang Regency was implemented starting November 24, 2011 simultaneously in all subdistricts in Rembang Regency, including in Sarang District, but its implementation has not been maximized. Therefore, the purpose of this study was to see the performance of PKH in the field of education in alleviating poverty in Sarang District, Rembang Regency. This study conducted a retrospective evaluation to see again whether PKH assistance in education had achieved its goals. The research method used is qualitative with data collection techniques through interviews, documentation, and observation. The results showed that the target of PKH beneficiaries in Sarang District had reached 95% on target, but for the effectiveness of PKH assistance, PKH beneficiaries had utilized the financial assistance provided to meet school needs and needs, but some were used for daily needs. day. In addition, the problem of disbursing aid funds experiencing delays and dependence on receiving assistance makes it difficult for PKH beneficiaries to carry out socialization and education for PKH membership graduation. Suggestions in this study are monitoring and mentoring to ensure that any assistance funds provided are properly used and awareness for PKH beneficiaries to want to graduate when their welfare has increased so that they are no longer dependent on the assistance provided.